PENGARUH PENAMBAHAN TEPUNG Azolla microphylla DAN TEPUNG SISA PENGGORENGAN TERHADAP KUALITAS KARKAS ITIK PEDAGING - Bashoirul Bashoirul; Alfan Setya Winurdana; Nita Ari Kustanti (Universitas Islam Balitar, 2021)
The purpose of this study is to determine the effect of the addition of azolla flour (Azolla michrophylla) on the percentage of carcass, abdominal fat, and giblet weight. The data obtained is analyzed variously with the ANOVA test and if there is a real effect of treatment, then continued with the Honest Real Difference (BNJ) test to find out the difference between treatments. The results of the study obtained by the addition of azolla flour had no effect on the percentage of carcass and giblet weight but had a noticeable effect on the percentage of abdominal fat. From the results of the best carcass percentage analysis obtained in P3 treatment, namely (59.09 ± 4.75%) with the addition of azolla flour by 30% without concentrate. At giblet weight the best percentage lies in the P1 treatment of (118.75 ± 25.51) this is suspected because the feed rations given contain azolla flour and concentrate with the same amount of 10%.The addition of azolla flour showed a noticeable effect (P>0.05) in lowering the abdominal fat of broilers located in P1, P2, P3, and P4.